A history of Old English literature - Fulk, R. D. (Robert Dennis); Cain, Christopher M. (Chichester : Wiley-Blackwell, 2013)
This revised edition of A History of Old English Literature draws extensively on the latest scholarship to have evolved over the last decade. The text incorporates additional material throughout, including two new chapters on Anglo-Saxon manuscripts and incidental and marginal texts. This revised edition responds to the renewed historicism in medieval studiesProvides wide-ranging coverage, including Anglo-Latin literature as well as non-canonical writingsIncludes new chapters on manuscripts and on marginal and incidental textsIncorporates expande.
Introduction: Anglo-Saxon England and its literature: a social history -- The chronology and varieties of Old English literature -- Anglo-Saxon manuscripts -- Literature of the Alfredian period -- Homilies -- Saints? legends (Rachel S. Anderson) -- Biblical literature -- Liturgical and devotional texts -- Legal texts -- Scientific and scholastic texts -- Wisdom literature and lyric poetry -- Germanic legend and heroic lay -- Additions, annotations, and marginalia -- Conclusion: Making Old English new: Anglo-Saxonism and the cultural work of Old English literature.
Includes bibliographical references and index.
Print version record and CIP data provided by publisher.
Keywords: To 1500; English literature -- Old English, ca. 450-1100 -- History and criticism; Christian hagiography -- History -- To 1500.; LITERARY CRITICISM -- European -- English, Irish, Scottish, Welsh; Christian hagiography; English literature -- Old English; Electronic books; Criticism, interpretation, etc; History